Loneliness among refugees: a neglected crisis in need of scalable innovation - Liu, Shuyan; Bromberg, Daniel J.; Haucke, Matthias; Zhou, Xin; Poole, Danielle N.; Bärnighausen, Till; Altice, Frederick L. (The lancet. Regional health, 2025)
Loneliness is increasingly recognized as a critical determinant of health, with the U.S. Surgeon General recently declaring it a public health crisis, comparable in impact to smoking and excessive alcohol consumption.1 While loneliness is widespread globally, it is particularly pervasive among forcibly displaced populations. Refugees fleeing conflict, persecution, or disaster are often separated from family and social networks, placed in unfamiliar environments, and face linguistic, cultural, and structural barriers to integration.2,3 These conditions place them at heightened risk for persistent loneliness, with cascading effects on physical and mental health.
Online verfügbar: 17. Juni 2025, Artikelversion: 17. Juni 2025
Gesehen am 12.01.2026